“My Struggles Matter”: a phenomenological analysis of young adults recovering from major depression - Chan, S.L.; Fonny, D.H.; Lau, P.L. (Faculty of Medicine, Universiti Malaya, 2021)
An alarming increase in the prevalence of depression has been found among Malaysian young adults which necessitates responsiveness. This study sought to better understand the subjective personal growth experience in terms of the processes among young adults recovering from major depressive disorder (MDD). A qualitative, transcendental phenomenological design was adopted by collecting data through in-depth, semi-structured interviews, audio recordings, interview transcripts and documents. Nine Malaysian young adults with MDD (Mean age=28) who reported being in recovery from MDD for at least one year were recruited from local mental health settings through purposive sampling. Data analysis involved Colaizzi’s eight-step method. The findings revealed eight personal growth processes themes: revealing the struggles, self-discovery and personal strength, personal responsibility, readiness for change, hope, redefining the meaning, forgiveness, and acceptance. Noticeably, each theme was interconnected to facilitate personal growth among major depressive young adults. The implications for mental health psychotherapy practice and future research were discussed.